Humic Substances Mediate Anaerobic Methane Oxidation Linked to Nitrous Oxide Reduction in Wetland Sediments - Valenzuela, Edgardo I.; Padilla-Loma, Claudia; Gómez-Hernández, Nicolás; López-Lozano, Nguyen E.; Casas-Flores, Sergio; Cervantes, Francisco J. (Frontiers in Microbiology, 2020)
Humic substances are redox-active organic molecules, which play pivotal roles in several biogeochemical cycles due to their electron-transferring capacity involving multiple abiotic and microbial transformations. Based on the redox properties of humic substances, and the metabolic capabilities of microorganisms to reduce and oxidize them, we hypothesized that they could mediate the anaerobic oxidation of methane (AOM) coupled to the reduction of nitrous oxide (N2O) in wetland sediments. This study provides several lines of evidence indicating the coupling between AOM and the reduction of N2O through an extracellular electron transfer mechanism mediated by the redox active functional groups in humic substances (e.g. quinones). We found that the microbiota of a sediment collected from the Sisal wetland (Yucatán Peninsula, southeastern Mexico) was able to reduce N2O (4.6±0.5 µmol N2O g sed.-1 day-1) when reduced humic substances were provided as electron donor in a close stoichiometric relationship. Furthermore, a microbial enrichment derived from the wetland sediment achieved simultaneous 13CH4 oxidation (1.3±0.1 µmol 13CO2 g sed.-1 day-1) and N2O reduction (25.2±0.5 µmol N2O g sed.-1 day-1), which was significantly dependent on the presence of humic substances as an extracellular electron shuttle. Taxonomic characterization based on 16S rRNA gene sequencing revealed Acinetobacter (a ɣ-proteobacterium), the Rice Cluster I from the Methanocellaceae and an uncultured archaeon from the Methanomicrobiaceae family as the microbes potentially involved in AOM linked to N2O reduction mediated by humic substances. The findings reported here suggest that humic substances might play an important role to prevent the emission of greenhouse gases (CH4 and N2O) from wetland sediments. Further efforts to evaluate the feasibility of this novel mechanism under the natural conditions prevailing in ecosystems must be considered in future studies.